2007
DOI: 10.1021/jp0752567
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and Discharge-Driven Pathways to Aromatic Products from 1,3-Butadiene

Abstract: A detailed study of the photochemical and discharge-driven pathways taken by gas-phase 1,3-butadiene has been carried out. Photolysis or discharge excitation was initiated inside a short reaction tube attached to the outlet of a pulsed valve. Bath gas temperatures near 100 K were achieved in the reaction tube by the constrained expansion of the gas mixture into the tube, simulating temperatures of relevance in Titan's atmosphere. Photolysis of 1,3-butadiene was initiated at 218 nm with a laser pulse that count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 71 publications
0
54
0
Order By: Relevance
“…In combustion environments, propargyl (C 3 H 3 ) recombination is generally thought to be one of the main benzene formation pathways [4,[11][12][13]. However, several studies have shown that benzene is a minor, or non-existent, product of propargyl recombination at low temperatures and pressures [12,14]. The C 3 H 3 + C 3 H 3 route to C 6 H 6 can only proceed by relatively inefficient radiative association in the very low pressures of astrochemical environments and so alternative mechanisms must be invoked.…”
Section: Introductionmentioning
confidence: 99%
“…In combustion environments, propargyl (C 3 H 3 ) recombination is generally thought to be one of the main benzene formation pathways [4,[11][12][13]. However, several studies have shown that benzene is a minor, or non-existent, product of propargyl recombination at low temperatures and pressures [12,14]. The C 3 H 3 + C 3 H 3 route to C 6 H 6 can only proceed by relatively inefficient radiative association in the very low pressures of astrochemical environments and so alternative mechanisms must be invoked.…”
Section: Introductionmentioning
confidence: 99%
“…24 The aromatic, bicyclic indane molecule as well as its α-methylstyrene (2-phenylpropene) and 1-phenylpropene isomers are considered as important reaction intermediates and toxic byproducts in the combustion of fossil fuel ( Figure 1). 11,12,[25][26][27][28][29][30][31][32] The reaction of the phenyl radcial (C 6 H 5 ) with propylene (C 3 H 6 ) presents a potential synthetic routes to synthesize C 9 H 10 isomers and to access the C 9 H 11 potential energy surface.…”
Section: Introductionmentioning
confidence: 99%
“…Propargyl radical (C 3 H 3 ), one of the smallest RSRs, has been of great interest in the formation of benzene both experimentally 1 and in theoretical models. 2 In recent ground-breaking work, Schmidt and co-workers spectroscopically characterized the doubly resonance-stabilized 50 1-phenylpropargyl radical, 5,6 with its benzylic radical site linking the phenyl and ethynyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…As a doubly resonance-stabilized radical, 1-phenylallyl possesses the same energetic benefits as [1][2][3][4][5][6][7][8][9][10] phenylpropargyl, and therefore may play a role of similar importance in pathways that lead from benzene to indene, naphthalene and beyond to larger PAHs. From an electronic structure viewpoint, 1-phenylallyl is also a close analog of the 1-hydronaphthyl radical, 3, 4 which is !-isoelectronic with 1-15 phenylallyl in its cis form.…”
Section: Introductionmentioning
confidence: 99%